Robust and flexible Internet connectivity for mobile ad hoc networks - Nordström, Erik; Gunningberg, Per; Tschudin, Christian (Ad hoc networks, 2011)
An important challenge for the wider adoption of mobile ad hoc network (MANET) technologies is finding ways to efficiently interconnect them with the Internet. However, such interconnections prove difficult due to differences in mobility, addressing and routing between MANETs and existing IP networks. In this paper, we review the existing solutions to interconnect MANETs with the Internet, but find them lacking in robustness and flexibility. For instance, many solutions do not consider the presence of multiple gateways, and in such scenarios they either fail, or are less efficient due to the lack of multi-homing capabilities. A key insight of ours is that the reason for routing failure is usually an interconnection scheme’s inability to express indirection (i.e., a way to enforce routing through a certain gateway on the path toward a destination in the Internet). Another problem concerns state replication where a route update fails to replicate all the routing state needed to forward packets to an Internet gateway. We analyze the above problems and suggest a solution that provides robust and flexible Internet connectivity. With minor adaptions our solution works for any MANET routing protocol, and has support for multiple gateways and multi-homing. Simulations show that, when used in combination with AODV routing, our solution provides up to 20% delivery ratio improvement over one of the main alternatives. A prototype implementation illustrates the feasibility of our solution in the real world.